THE INFLUENCE OF DIGITAL FINANCE ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN UGANDA - ADONGO BRIDGET (UGANDA CHRISTIAN UNIVERSITY, 2025)
The influence of digital finance on small and medium businesses in Mukono is, therefore, analyzed in this paper to appreciate how such digital finance technology influences business performance. The study further discovered the use of Digital Finance by SMEs which has great benefits, bettering transaction speed, minimizing operational costs and maximizing revenue growth. The research, in its findings shows the use of digital financial services and how this technology is of great advantages to the small medium businesses though there are small challenges involved when using these services like fraud, network issues and inadequate technical skills. This study merges both quantitative and qualitative approaches in data collection to measure the effectiveness of digital financial services and also identifies the barriers faced. From the findings, it is observed that overcoming the challenges is very important for full benefits of digital financial technologies. The research shows that digital financial services need to be combined with the business operations for better performance and growth of the businesses. This calls for support and combined effort from the service providers, government and other stakeholders for the growth of the small medium businesses
UNDERGRADUATE RESEARCH